The Origins of the Grand Alliance : Anglo-American Military Collaboration from the Panay Incident to Pearl Harbor - Johnsen, William Thomas, 1952- (Book collections on Project MUSE., 2016)
This work provides comprehensive analysis of military collaboration between the United States and Great Britain before the Second World War. William T. Johnsen sets the stage by examining Anglo-French and Anglo-American coalition military planning from 1900 through World War I and the interwar years. He also considers the formulation of policy and grand strategy, operational planning, and the creation of the command structure.